The truncated phage lysin CHAP(k) eliminates Staphylococcus aureus in the nares of mice - Fenton, Mark (Landes Bioscience, 2010)
The endolysin LysK derived from staphylococcal phage K has previously been shown to have two enzymatic domains, one of which is an N-acetylmuramoyl-L-alanine amidase and the other a cysteine/histidine-dependant amidohydrolase/peptidase designated CHAP(k). The latter, when cloned as a single-domain truncated enzyme, is conveniently overexpressed in a highly-soluble form. This enzyme was shown to be highly active in vitro against live cell suspensions of S. aureus. In the current study, the IVIS imaging system was used to demonstrate the effective elimination of a lux labeled S. aureus from the nares of BALB/c mice.